FRI0565-HPR Shoulder Function is Impaired in Early Rheumatoid Arthritis- A Controlled Study. (10th June 2014) - Bilberg, A.; Bremell, T.; Balogh, I.; Mannerkorpi, K.
Abstract : Background: Patients with rheumatoid arthritis (RA) risk impaired shoulder function due to the inflammatory process. Despite improved pharmacological treatment, patients with early RA report difficulties with activities involving the shoulder. Objectives: To compare shoulder function and activity limitation related to the shoulder, arm and hand in women with early RA compared to age-matched healthy women. Methods: This controlled cross-sectional study included 103 women with early rheumatoid arthritis and a reference group of 103 age-matched healthy women. The mean age was 47.1 (SD 10.0) years, the mean disease duration was 20.3 (SD 8.5) months and the mean DAS28 score was 3.8 (SD 1.4) among the patients. Measurements: Shoulder function was assessed by isometric shoulder muscle strength, active shoulder-arm movement, and activity-induced shoulder pain. Hand-grip force was also recorded. Activity limitations related to the upper extremities were assessed with the Disability of the Arm, Shoulder and Hand (DASH) questionnaire (1), and disease activity by the DAS28 score. Statistics: Data are presented as mean, standard deviation, median, range and number and percentage. For comparison between groups non parametric statistic was used. The Spearman's correlation coefficient was used to analyse the associations between shoulder muscle strength and other assessments Results: Patients showed significantly (p<0.0001) impaired shoulder muscle strength, shoulder-arm movement, and shoulder pain compared to the reference group. Patients shoulder muscle strength was approximately 65% of the results observed in the reference group. Activity limitations related to the shoulder, arm and hand (DASH) were significantly (p<0.0001) higher in the patient group compared to the reference group and indicates limitations in daily activities for the patients. Conclusions: Patients with early RA were found to have impaired shoulder function compared to age-matched subjects. Especially the shoulder muscle strength was reduced to 65% in the patient group. Shoulder muscle strength was found to be associated with activity limitations (DASH) implying that screening and monitoring of shoulder function, emphasising the shoulder muscle strength, should be initiated from disease onset. References: Hudak PL, Amadio PC, Bombardier C. Development of an upper extremity outcome measure: the DASH (disabilities of the arm, shoulder and hand) [corrected]. The Upper Extremity Collaborative Group (UECG). Am J Ind Med. 1996 Jun;29(6):602-8. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4988